Analysis of Factors Influencing Sports Participation in Adults: A Social-Ecological Model Approach - Okta, Setyo Luthfi; Nurnisaa (Corespub, 2025)
Sports participation in adults is an important component in maintaining individual health and well-being, but participation rates tend to decline with age, especially in developing countries such as Indonesia. This study aims to analyze factors that influence sports participation in adults using a socio-ecological model approach. Using a qualitative descriptive method through a case study design, this study involved 15-20 adult participants aged 25-60 years with varying levels of sports participation. Data collection was conducted through semi-structured interviews, observation, and documentation, then analyzed using the Miles and Huberman model. The results showed that sports participation was influenced by complex interactions of various levels of factors: (1) individual level (health motivation, self-perception of ability), (2) interpersonal level (social support, cultural norms), (3) organizational level (availability of facilities, welfare programs), (4) community level (supporting infrastructure, environmental safety), and (5) public policy level (physical activity promotion programs). This study concludes the importance of a multi-level and integrated approach to increasing adult sports participation by considering the socio-cultural context of Indonesia. Recommendations include developing educational programs, establishing sports communities, providing easily accessible facilities, developing safe public spaces, and formulating policies that support sports infrastructure and public awareness campaigns.